Politik dan HAM: Analisis Yuridis Regulasi Presidential Treshold Pemilihan Calon Presiden di Indonesia - Sari, Tika Puspita; Desiandri , Yati Sharfina (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2023)
Democracy in the government system places emphasis on power in the hands of the people; however, with the approval of election law number 7 of 2017 regarding the regulation of threshold requirements for presidential and vice presidential candidates, it is considered detrimental to the people because the additional conditions related to the administrative requirements for presidential and vice presidential candidates are deemed to be contradictory. With the 1945 Constitution Article 6A paragraph (2) and Article 28 D paragraph (3) on human rights, especially the right to participate in politics, the space for democracy is limited because, basically, Indonesian people have the right to vote and choose. In fact, it has been proven that there are only two candidates for president and vice president in the 2014–2019 and 2019–2024 election periods, forcing the public to choose the candidates that have been provided, even though these candidates are not necessarily the candidates that the public expects, thus giving the impression of forcing personal human rights to participate. in the presidential election. In this research, the author uses a normative legal research method in the form of a library search. The results of the research show that the nomination requirements regulated in the 1945 Constitution, Article 6A paragraph (2), do not regulate thresholds, but there are additional requirements in Article 222 that have become controversial, so that the threshold causes the loss of political rights to be able to suggest presidential and vice presidential candidates. Conflicts can destroy democracy. . Indonesia. People and political parties who want to run for the presidential election cross the threshold so that entering a presidential system gives rise to limited democracy. This is because national hopes still require a judicial review to guarantee the upholding of human rights, which hampers the process of emerging more alternative leadership candidates to realize people's welfare. From a benefit perspective, whatever government policy, must take into account the aspirations of its people, so that government policy must be in line with the public interest.